(untitled) - Patel, Mukund R. (Florida, 2005)
This edition includes two chapters devoted to new and specialized technologies. The third section explores large-scale energy storage technologies, overall electrical system performance, and total plant economy while the final section explores ancillary power systems derived from the sun
Keywords: Trạm năng lượng gió,Wind power plants,Trạm năng lượng mặt trời,Solar power plants